Assessment of clinical immunogenicity of inotuzumab ozogamicin in patients with non-Hodgkin lymphoma and acute lymphoblastic leukemia - Darshana Jani; John Nowak; Ying Chen; Joseph Boni; Boris Gorovits (SpringerOpen, 2018)
Abstract Introduction Inotuzumab ozogamicin (InO) is an antibody-drug conjugate composed of a recombinant, humanized immunoglobulin type G, subtype 4 (IgG4) antibody covalently bound to a semisynthetic derivative of calicheamicin via an acid-labile linker. It was developed for the treatment of relapsed or refractory non-Hodgkin lymphoma (NHL) and acute lymphoblastic leukemia (ALL). Based on the perceived relatively low immunogenicity risk for this product, a standard approach to immunogenicity testing was utilized during the clinical studies. This manuscript describes the analytical aspects of antibody measurement and highlights the immunogenicity data from clinical studies in patients with hematologic malignancies. Methods Anti-drug antibodies (ADAs) were determined using an enzyme-linked immunosorbent assay for patients with NHL and a bridging electrochemiluminescence assay for patients with ALL. ALL patients who tested positive for ADA were also tested for neutralizing antibodies (pivotal studies only) using a cell-based assay. Results Immunogenicity assays were validated per current industry practice and regulatory guidelines. Positive ADAs were observed in 7 of 164 (4%) patients with ALL during the pivotal trial. Neutralizing antibodies were not detected in any patients with positive ADAs. No ADAs were detected during the phase I/II ALL study. In NHL studies, antibodies to InO were observed in 27 of 630 (4%) patients. InO clearance was similar between ADA-positive and ADA-negative ALL patients. Conclusion Standard immunogenicity strategy provided data to evaluate impact on InO efficacy, pharmacokinetics, or other clinical parameters in patients. The incidence of ADA to InO is low and is not clinically meaningful.